2023
DOI: 10.1002/hsr2.1537
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile, ox‐LDL, and LCAT activity in patients with endometrial carcinoma and type 2 diabetes: The effect of concurrent disease based on a case–control study

Reihane Qahremani,
Soghra Rabizadeh,
Hossein Mirmiranpoor
et al.

Abstract: Background and AimThe role of lecithin: cholesterol acyltransferase (LCAT) and oxidized low‐density lipoprotein (ox‐LDL) in endometrial cancer (EC) or EC with concurrent type 2 diabetes is still unclear. This study investigated the LCAT activity, ox‐LDL, and lipid profile in EC patients with or without type 2 diabetes and compared them with healthy individuals and patients with type 2 diabetes alone.MethodsIn this cross‐sectional, case–control study, 93 female participants were recruited. The participants were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…ApoA1, as one of the main components of HDL-C, plays a vital role in the formation of most plasma-esterified cholesterol and helps to promote cholesterol efflux from tissues to the liver by being a cofactor for lecithin cholesterol acyl transferase (LCAT) [ 19 , 20 ]. ApoA1 modulates LDL-C function and its clearance by the liver.…”
Section: Introductionmentioning
confidence: 99%
“…ApoA1, as one of the main components of HDL-C, plays a vital role in the formation of most plasma-esterified cholesterol and helps to promote cholesterol efflux from tissues to the liver by being a cofactor for lecithin cholesterol acyl transferase (LCAT) [ 19 , 20 ]. ApoA1 modulates LDL-C function and its clearance by the liver.…”
Section: Introductionmentioning
confidence: 99%
“…So far, several pieces of research have been conducted on the effects of low HDL levels on cancer, cardiovascular events, and diabetes [ 16 , 23 25 ]. Recent studies have reported failure in reducing cardiovascular events, insulin resistance, diabetic retinopathy, cancer mortality rate, and unexpectedly increasing mortality in subjects with elevated HDL‐C levels [ 7 , 13 , 14 , 26 ].…”
Section: Introductionmentioning
confidence: 99%